The Sexual Assault Forensic Examination Telehealth (SAFE‐T) Center: A Comprehensive, Nurse‐led Telehealth Model to Address Disparities in Sexual Assault Care. Issue 1 (8th June 2020) - Miyamoto, Sheridan; Thiede, Elizabeth; Dorn, Lorah; Perkins, Daniel F.; Bittner, Cynthia; Scanlon, Dennis
Abstract: Background: Rural and underserved communities often struggle to provide access to specialized health care, including sexual assault care. Telehealth is an effective solution for providing access to an array of specialized health care services. Prior sexual assault telehealth programs have provided evidence that telehealth is a feasible and acceptable solution. However, there is scant information about program development and considerations in the literature to guide those who may seek to implement a sexual assault telehealth program in their communities. Purpose: The purpose of this paper is to describe the Sexual Assault Forensic Examination Telehealth (SAFE‐T) Center—a nurse‐led model for providing comprehensive, high‐quality sexual assault care in rural and underserved communities recently implemented at 3 hospitals in rural Pennsylvania. Methods: Using the program's logic model, we present our community‐engaged approach to the development and implementation phases of the SAFE‐T Center. Findings: We first describe how academic researchers partnered with multiple stakeholders to form a statewide advisory board and articulated a vision and mission for the SAFE‐T Center that meets the needs of local communities. We then describe the overall design of the model, how it was informed by this academic‐community partnership, and how each element relates to anticipated outcomes. We also present our plans for program evaluation, expansion, and sustainability. Conclusion: This detailed description of collaborative partnership, coalition‐building, program design and implementation can serve as a guide for hospitals and health systems seeking to implement telehealth programs to improve the care provided to survivors of sexual assault.